Inclusive Cybersecurity Literacy in Cybercrime Prevention Among MSME Operators in Lhokseumawe - Safwan Safwan; Nur Sari Dewi; Nora Maulana; Friyal Dara Azkia; Nur Zahra Azira (Transformatif: Jurnal Pengabdian Masyarakat, 2026)
Digital The rapid digitalization of Micro, Small, and Medium Enterprises (MSMEs) has increased exposure to cyber threats, while limited cybersecurity literacy remains a major challenge for business sustainability. This community service program developed and evaluated a contextual cybersecurity mentoring model designed to strengthen digital security awareness and practices among MSME owners in Lhokseumawe, Indonesia. Using a Participatory Action Research (PAR) approach, the program integrated needs assessment, cybersecurity education, hands-on training, and continuous mentoring tailored to the actual cyber risks faced by MSMEs. Sixty MSME operators under the Rumah BUMN Lhokseumawe participated in the program. Effectiveness was assessed using pre- and post-test instruments and analyzed through paired-sample t-tests and normalized gain (N-Gain). The results demonstrated a significant improvement in participants’ cybersecurity literacy, with mean scores increasing from 41.45 before the intervention to 93.25 afterward (p < 0.001). The N-Gain score of 0.876 indicated a high level of learning effectiveness. Participants also showed substantial improvements in cybersecurity knowledge, digital security practices, and risk awareness, enhancing their capacity to prevent cyber threats and strengthen business resilience. The findings demonstrate that an adaptive, participatory, and locally contextualized mentoring model is an effective strategy for improving cybersecurity literacy among MSMEs. This model provides a scalable framework for supporting secure digital transformation and can be replicated in MSME empowerment initiatives across other regions.